The Influence Of Financial Literacy And Lifestyle On The Ability To Pay Spaylater Among Gen Z - Tambunan, Sagdiyah Fitri Andani; Nur Ahmadi Bi Rahmani; Aqwa Naser Daulay (LP2M IAIN Palopo, 2025)
This study aimed to analyze the influence of financial literacy and lifestyle on SPaylater repayment capacity among Generation Z residing in Medan. The research method used was an associative quantitative survey approach, involving 100 participants selected using a purposive sampling technique. The research findings indicate that financial literacy has a significant positive impact on respondents' capacity to fulfill SPaylater payment obligations. Furthermore, lifestyle also makes a significant positive contribution to this payment capacity. These two variables, both individually and collectively, have been shown to significantly contribute to explaining variations in Generation Z's ability to fulfill digital payment obligations. These findings emphasize the importance of improving financial literacy and adopting a better and wiser lifestyle so that the younger generation can better manage their finances in the face of the development of digital financial services such as SPaylater.